2008
DOI: 10.1038/modpathol.3800995
|View full text |Cite
|
Sign up to set email alerts
|

Phospho-S6 ribosomal protein: a potential new predictive sarcoma marker for targeted mTOR therapy

Abstract: Metastatic sarcomas are commonly resistant to chemotherapy. The serine/threonine kinase, mammalian target of rapamycin (mTOR), is a protein kinase of the phosphatidylinositol 3-kinase (PI3K)/AKT signaling pathway thought to have a key role in controlling cancer growth and thus is an important target for cancer therapy. Several inhibitors of mTOR are in clinical trials, including AP23573, which is being tested on metastatic sarcomas and other tumors. We hypothesized that a marker for the activity of mTOR, phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(94 citation statements)
references
References 28 publications
5
89
0
Order By: Relevance
“…In addition, p-S6 expression was predictive of the early sarcoma response to AP23573, an inhibitor of mTOR, 30 suggesting that the status of p-S6 in solid tumors influences the response to anticancer therapy. In this regard, our findings extend the clinical role of p-S6 by demonstrating that elevated p-S6 and an elevated p-S6/S6 ratio are associated with poor clinical outcome of patients with early stage esophagus squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, p-S6 expression was predictive of the early sarcoma response to AP23573, an inhibitor of mTOR, 30 suggesting that the status of p-S6 in solid tumors influences the response to anticancer therapy. In this regard, our findings extend the clinical role of p-S6 by demonstrating that elevated p-S6 and an elevated p-S6/S6 ratio are associated with poor clinical outcome of patients with early stage esophagus squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 It was originally identified as the target of the antibiotic rapamycin (Rapamune, Wyeth pharmaceuticals, Madison NJ, USA). 12 Subsequent studies revealed a broad spectrum of functions for this molecule, including cell cycle progression, cell proliferation, angiogenesis, and apoptosis.…”
Section: Mtor and Its Role In Cellular Processesmentioning
confidence: 99%
“…19,22,28 Activated mTOR can subsequently phosphorylate p70 S6 kinase-1 (p70 S6K) and 4E-BP. p70 S6K, a serine/threonine kinase, phosphorylates the ribosomal protein S6 of the 40S ribosomal subunit at Ser235 and 236 to increase translation of 5 0 terminal oligopyrimidine tract mRNAs 10 and also binds to mitochondrial membranes and inactivates the pro-apoptotic molecule BAD. 11,20 Phosphorylation of 4E-BP allows assembly of the translational initiation complex with subsequent translation of proteins necessary for progression of the cell cycle past the G1 phase, such as cyclin D1.…”
Section: Mtor and Its Role In Cellular Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…mTOR activates S6 kinase 1 (S6K1), a kinase involved in protein synthesis, and inhibits the 4-E binding protein (4EBP1), a translational repressor [115] and possible tumor suppressor [116]. There is a suggestion that phosphorylated mTOR expression is a poor prognostic marker because it has been associated with worse disease-free survival in a small cohort [117].…”
Section: Mammalian Target Of Rapamycinmentioning
confidence: 99%